(3QSGdI aj aVd LOI GdeYehQI hGdeQGHW ajgG hMhGdjgGs - (3LGQ Gddg Hf agO Gdecj GdYdhjs ((3YHO Gddg Hf YHO GdhGMO GdYHO GdSdGe GdYHGSi GdchGRi GdTGaYi GdHUQi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO abO PcQ GdYdGeI GdePchQ BfakG ef aVd LOI GdeYehQI SGMd ecI GdeTQaI s
(3BNQgG (B:s
(3Cfg jUjQ GdHGbi ef GdCUdi ddeGd GdhGQO TF bdjd hYdi gPG GdMGd Edi EfbVGA GdOhQGf aGdeXGde JRjO hMSHfG Gdgd hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B23s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHOGddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi (B1294 (3g`s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs